Progressive and game-based training approach in basketball learning: the role of students' motor skills - Riang Hari Ramadhan; Arsil Arsil; Anton Komaini; Ronni Yenes (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examined the effect of Progressive and Game-Like training methods on the shooting ability of Padang State University basketball players, considering motor skill levels (high vs low). A quasi-experimental 2x2 factorial design was used with 20 purposively selected players. Shooting ability was measured using the Basketball Jump Shooting Accuracy Test, and motor skills were assessed with the Barrow Motor Ability Test. Data analysis using two-way ANOVA revealed a significant effect of training methods on shooting ability (F = 31.296; p < 0.05) and a significant interaction between training methods and motor skill levels (F = 76.406; p < 0.05). The Game-Like Method was more effective for players with high motor skills, while the Progressive Method benefited players with low motor skills. These results highlight the importance of tailoring training methods to individual motor characteristics and suggest careful consideration of sample limitations and context in interpreting effectiveness.